City Branding as a Concept for the Regional Tourism Development (Research, Society and Development, 2019)
City Brand is an identity, symbol, logo, or merk of a particular city which has aimed to look for the specialty of certain city. The specialty of city is used as a society product to attract tourists, investors, residents, and talented people. Thus, the objectives of this study is try to determine the positioning and making the city branding in Bangkalan, East Java, Indonesia. The expected target is the improvement of society awareness toward tourism object and the renovation of tourism object in Bangkalan. Furthermore, this study is conducted for 3 years started with the collection of primary data. This primary data will be the material of analysis in the second year. The results of the previous analysis will be the basis for the implementation of the third-year study. In addition, this study is also used survey, field research, interview with some elements of society, investigate the real condition of tourist destination and tourism stakeholders in Bangkalan. Afterwards, the result of this study shows the lack of readiness from the government in mapping the area and the concept of tourism in Bangkalan. Moreover, the society awareness to maintain the security and comfort of tourism place are also an obstacle to create city branding in Bangkalan. But religious tourism can be developed as proper as the jargon of Bangkalan itself.